2023
DOI: 10.3390/nu15214628
|View full text |Cite
|
Sign up to set email alerts
|

Association between Gut Microbiota and Breast Cancer: Diet as a Potential Modulating Factor

Duygu Altinok Dindar,
Brie Chun,
Amy Palma
et al.

Abstract: Breast cancer (BCa) has many well-known risk factors, including age, genetics, lifestyle, and diet; however, the influence of the gut microbiome on BCa remains an emerging area of investigation. This study explores the connection between the gut microbiome, dietary habits, and BCa risk. We enrolled newly diagnosed BCa patients and age-matched cancer-free controls in a case-control study. Comprehensive patient data was collected, including dietary habits assessed through the National Cancer Institute Diet Histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…[3][4][5][6] Within this array of factors, there is a growing body of evidence highlighting the significance of dietary factors in breast cancer development. [7][8][9] Both experimental studies and human data have indicated that high consumption of dietary fat is linked to an increased incidence of the disease and elevated breast cancer risk. [10][11][12] Our particular interest is saturated fatty acids (SFAs), a specific group of fatty acids characterized by the absence of double bonds between carbon atoms.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6] Within this array of factors, there is a growing body of evidence highlighting the significance of dietary factors in breast cancer development. [7][8][9] Both experimental studies and human data have indicated that high consumption of dietary fat is linked to an increased incidence of the disease and elevated breast cancer risk. [10][11][12] Our particular interest is saturated fatty acids (SFAs), a specific group of fatty acids characterized by the absence of double bonds between carbon atoms.…”
Section: Introductionmentioning
confidence: 99%